PERAN BALAI PENYULUHAN PERTANIAN (BPP) DALAM PENYULUHAN KOMODITI PANGAN (STUDI KASUS DI KABUPATEN TANAH DATAR) - Wahyuni, Sri; Helmi, Helmi; Tanjung, Hery Bachrizal; Oktavia, Yenny (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
The process of achieving food security in Indonesia is inseparable from the role of extension as the educative technical personnel and empowerment of farmers. The extention is incorporated and authorized into the agricultural scope organization unit to carry out extension activities, one of which is the AEC. The research aims to look at the role of the AEC in extention food commodities. This type of research was descriptive which was designed qualitatively using the focus group discussion (FGD) method which aimed to explored specific problems related to the role of the AEC in Tanah Datar District. The results showed that the AEC in Tanah Datar District had carried out its role in conducting food commodity counseling well, but it was still not optimal due to limited facilities and infrastructure, accommodation and financing, and lack of resources and extension staff. In addition, the role of extensions has only reached the aspect of providing inputs, cultivation and harvesting. Extensions had not fully helped independent farmers in marketing matters. Therefore, it is important to increase the role of extension agents so that they can carry out their functions properly in conducting food commodity counseling.